2003
DOI: 10.1097/00002030-200308150-00016
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission of HIV in Rio de Janeiro, Brazil

Abstract: A cohort of 297 HIV-infected pregnant women was followed from January 1996 to December 2001. The overall transmission rate was 3.57% and remained constant over time. Low birth-weight was independently associated with a higher risk of vertical transmission (P=0.0072), whereas a longer duration of antiretroviral drugs during pregnancy was independently associated with a lower risk of transmission (P=0.0084). Further decreases in transmission should be obtained by initiating prophylaxis earlier in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
26
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 6 publications
5
26
0
6
Order By: Relevance
“…This decline is similar to what has been reported in other studies both in-country and internationally (João et al 2003, Wade et al 2004, Matida et al 2005, Succi 2007), demonstrating the effectiveness of strategies aimed at reducing mother to child transmission. Results from a multicenter observational study conducted in Latin America and Caribbean countries that included 770 mother-infant exposed to different ART regimens (Read et al 2007) also demonstrated a low (0.91%, 95%CI: 0.37 -1.86) HIV-1 mother to child transmission rate.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This decline is similar to what has been reported in other studies both in-country and internationally (João et al 2003, Wade et al 2004, Matida et al 2005, Succi 2007), demonstrating the effectiveness of strategies aimed at reducing mother to child transmission. Results from a multicenter observational study conducted in Latin America and Caribbean countries that included 770 mother-infant exposed to different ART regimens (Read et al 2007) also demonstrated a low (0.91%, 95%CI: 0.37 -1.86) HIV-1 mother to child transmission rate.…”
Section: Discussionsupporting
confidence: 89%
“…However, other studies have reported low birth weight (LBW) and prematurity to be associated with mother to child transmission, and a possible explanation for the discrepancy could be the higher frequency of LBW and prematurity described in other populations (Nogueira et al 2001, João et al 2003, Magder et al 2005, Szyld et al 2006. However, neonatal diseases such as respiratory distress syndrome, sepsis, and neonatal jaundice were associated with HIV-1 vertical transmission indicating that others factors are associated with the newborn infection.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Há estudos de base hospitalar (ou de centros de referência) e estudos utilizando dados secundários com resultados divergentes, por conta da seleção prévia de gestantes já com diagnóstico de HIV nos primeiros, e a adição de casos notificados sem nenhuma intervenção para redução da transmissão vertical do HIV nos dados secundários. Exemplos de sucesso no Rio de Janeiro, com 2,8% de transmissão em uma coorte com 145 crianças 15 e outra com 3,6% entre 297 crianças 16 no Estado de São Paulo foi de 16% em estudo de base hospitalar 20 . Em 2006, no mesmo estado, houve uma redução para 2,7%, utilizando-se dados secundários, o que pode ser considerado um grande sucesso programático 21 .…”
Section: Discussionunclassified
“…19 After the introduction of antiretroviral therapy (ART) for the prevention of mother-to-child transmission of HIV-1 (PMTCT), a signifi cant reduction in the transmission rate was observed. A multicenter study reported a transmission rate of 7.1% in 2001, 12 although lower rates have been reported in single-center studies conducted in Southeastern Brazil. 13,14,18 The assessments of a child's weight at birth and of his or her growth are indicators of the child's nutritional status.…”
mentioning
confidence: 89%